Impact of biologics on disease course in systemic onset juvenile idiopathic arthritis - BARIŞ, HATİCE EZGİ (SPRINGER LONDON LTD, 2018)
To analyze our cohort of patients with systemic onset juvenile idiopathic arthritis (SoJIA) and investigate the impact of biologic disease-modifying antirheumatic drugs (BDMARDs) on disease course. Children who were diagnosed with SoJIA according to International League of Associations for Rheumatology (ILAR) criteria in Boston Children's Hospital between January 1996 and December 2015 were included. Data were collected from patients' charts retrospectively. Demographic features, disease course, and medication usage were identified. There were 76 patients who met ILAR criteria. Most common presenting features were fever (100%), arthralgia (92%), rash (87%), and arthritis (83%). Median follow-up was 69months. At last visit, 18% still had active disease. Disease course was monophasic in 18 patients (24%), persistent in 24 patients (32%), and polycyclic in 34 patients (45%). Thirty-three percent (n, 6) of children with monophasic disease was diagnosed before 2004 and 67% (n, 12) was diagnosed after 2004 (p=0.08). Sixty-six percent was treated with a BDMARD. Anakinra (37%) was the most common prescribed BDMARD. Monophasic disease was less common in patients treated with a BDMARD (n, 6, 12%) compared to children not treated with a BDMARD (n, 12, 46%) (p=0.01). BDMARDs are started earlier (r(s), -0.67; p<0.001) and diagnosis of SoJIA is made sooner after symptom onset in recent years (r(s), -0.37; p=0.001). Most patients in our cohort were able to achieve remission. Proportion of monophasic disease tends to increase after 2004 although not statistically significant. In recent years, physicians tend to diagnose SoJIA earlier and treat more aggressively early in the course of the disease with BMARDs. Future prospective research in larger cohorts investigating the effects of BDMARDs on disease course and predictive factors for outcome is needed.
Keywords: Anakinra; Clinically inactive disease; Macrophage activation syndrome; Morbidity; Remission; Systemic onset juvenile idiopathic arthritis; RHEUMATOID-ARTHRITIS; SELECT CATEGORIES; TOCILIZUMAB; ETANERCEPT; REMISSION; CHILDREN; OUTCOMES; COLLEGE; CLASSIFICATION; PREDICTORS